(untitled) (Eurasian Medical Research Periodical, 2023)
The paper presents current views on the etiology and pathogenesis of multiple myeloma. The article reviews the literature on epidemiology, mechanism of development, and risk factors for the development of the disease. Multiple myeloma is a malignant tumor of Bcell origin, the morphological substrate of which is plasma cells that produce its monoclonal immunoglobulin. Literature data show that multiple myeloma has an ambiguous distribution pattern, and there is a tendency for its annual growth. Although the etiology of multiple myeloma is not fully understood, according to most researchers, the risk factors leading to a progressive increase in the incidence of the population include old and senile age, male gender, and exposure to negative environmental factors. Longterm antigenic stimulation plays a certain role, which is confirmed by the increased frequency of multiple myeloma in patients with chronic and inflammatory diseases. It was revealed that cytokines and genetic aspects play an important role in the development of the disease. Характерными для Multiple myeloma is characterized by non-specific symptoms and similarity of its clinical manifestations with other diseases, which is one of the reasons for late diagnosis. Injuries to internal organs, in particular the heart and kidneys, arene of the most frequent complications of multiple myeloma, the combined occurrence of which leads not only to mutual aggravation, but also is one of the factors of early adverse outcomes. Despite the research conducted to date, much of the pathogenesis of multiple myeloma has not been disclosed, which dictates the need for a more in-depth and comprehensive study of the problem